Relações públicas e o Brand Management: storytelling 2.0 na construção de relacionamentos - Sousa, Mariana Rodrigues de [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
According to the Informational Society of the twentieth century, man develops society of the spectacle, where life becomes virtual and the individual ceases to be a spectator becoming the protagonist of wikiciberepopéia and organizations seeking to gain the attention and time of its consumers through new communication strategies. If the great epics of mankind brought mythical heroes, divine, with powers (mostly above the mortals), in the era of new technologies, the common man is in the hands the opportunity to become the hero of his own ciberepopéia. Increasingly resistant to traditional advertising, the new model of media consumer, the prosumer, the storytelling is transforming into one of the main communication tools of contemporary organizations. Offer your audience a creative and relevant content across several media platforms is a major brand positioning strategies currently used, in addition to providing the transmission of values and organizational principles in a subjective manner. Storytelling where objects are extensions of the human body (eg, the cell can be treated as an extension of the ears) is a strong indication of a technocratic society, because we can consider the new technologies as extensions of the human brain (as new store technologies, create meanings, share information through a specific language) and the individual who is on the edge of new technology ends up being excluded from certain social events. This new world tends to put an end to separation between seemingly contrary ideas, such as reality/fiction, natural/cultural and the man who emerges from this medium is not the creator, but rather, transforming what already exists. The current human evolution takes place from about half the human mind and tell stories that go beyond the media saturation that really emocionem and who have a real meaning for those who listen, to be interconnected with the socio-environmental reality of this new consumer, is a major chall...

Segundo a Sociedade Informacional do século XX, o homem desenvolve a sociedade do espetáculo, onde a vida se torna virtual e o indivíduo deixa de ser espectador transformando-se em protagonista da wikiciberepopéia e as organizações buscam conquistar a atenção e o tempo dos seus consumidores através de novas estratégias comunicacionais. Se as grandes epopéias da humanidade traziam heróis míticos, divinos, com poderes (na maioria das vezes acima dos mortais), na era das novas tecnologias, o homem comum tem nas mãos a oportunidade de tornar-se o herói da sua própria ciberepopéia. Cada vez mais resistentes à propaganda tradicional, o novo modelo de consumidor de mídia, o prosumidor, está transformando o storytelling em uma das principais ferramentas de comunicação das organizações contemporâneas. Oferecer ao seu público-alvo um conteúdo criativo e relevante através de diversas plataformas midiáticas é uma das principais estratégias de posicionamento da marca utilizadas atualmente, além de proporcionar a transmissão dos valores e dos princípios organizacionais de maneira subjetiva. Contar histórias onde os objetos são extensões do corpo humano (como por exemplo, o celular pode ser tratado como extensão dos ouvidos) é um forte indício de uma sociedade tecnocrata, pois já podemos considerar as novas tecnologias como extensões do cérebro humano (pois as novas tecnologias armazenam, criam significados, compartilham informações através de uma linguagem específica) e aquele indivíduo que fica à margem das novas tecnologias acaba sendo excluído de determinado convívio social. Este mundo novo tende a por um fim na separação entre ideias aparentemente contrárias, tais como realidade/ficção, natural/cultural e, o homem que emerge desse meio não é criador, mas sim, transformador do que já existe. A atual evolução humana se dá a partir da relação meio-mente humana e contar histórias que superem...
Keywords: Organização; Relações publicas; Arte de contar historias; Comunicação nas organizações; Comunicação - Pesquisa; Marketing; Gestão de negócios; Organization